INRRI-EDM/2016: the first laser retroreflector on the surface of Mars. Issue 2 (15th January 2017) - Dell'Agnello, S.; Delle Monache, G.; Porcelli, L.; Boni, A.; Contessa, S.; Ciocci, E.; Martini, M.; Tibuzzi, M.; Intaglietta, N.; Salvatori, L.; Tuscano, P.; Patrizi, G.; et al.
Abstract: During Summer 2015 the SCF_Lab (Satellite/lunar/GNSS laser ranging/altimetry and cube/microsat Characterization Facilities Laboratory, www.lnf.infn.it/esperimenti/etrusco ) Team of INFN-LNF, with support by ASI, carried out an intense activity of final design, manufacturing and testing in order to construct, space qualify and finally integrate INRRI-EDM/2016 on ESA's ExoMars EDM spacecraft (also dubbed 'Schiaparelli'), which was successfully launched on March 14, 2016. INRRI (INstrument for landing-Roving laser Retroreflector Investigation) for the EDM (Entry descent and landing Demonstration Module) 2016 mission is a compact, lightweight, passive, maintenance-free array of eight cube corner laser retroreflectors fixed to an aluminum alloy frame through the use of silicon rubber suitable for space applications. INRRI was installed on the top panel of the EDM Central Bay on October 14, 2015. It will enable the EDM to be laser-located from Mars orbiters, through laser ranging and altimetry, lidar atmospheric observations from orbit, laser flashes emitted by orbiters, and lasercom. One or all of the above means of observation can be supported by INRRI when there is an active, laser-equipped orbiter, especially after EDM end-of-life and for a long time. INRRI goals will cover science (Mars geodesy/geophysics, future Mars test of General Relativity, GR), technology and exploration. Concerning the latter two, INRRI will support mars-georeferencing of the EDM landing site, support potential precision lidar-based landing next to the EDM, support test & diagnostics of lasercom for data exchange among Mars orbit, Mars surface and Earth, and it will be a precursor for additional Mars surface retroreflectors, for example on exploration rovers. This paper describes in detail our innovative payload, hopefully the very first to be deployed safely with the lander Schiaparelli on the Mars surface, and its space qualification for the ExoMars EDM 2016 mission. Despite the fate of the Schiaparelli landing, which is still under the investigation of ESA and the industry, this paper remains a valuable reference for next INRRI-like laser retroreflectors arrays.